Philippe Josserand. Jacques de Molay. Le dernier grand-maître des Templiers. Édition revue et augmentée. Paris: Les Belles Lettres, 2023. 541 pp. ISBN: 978-2-251-44977-7.: Philippe Josserand. Les sept vies de Jacques de Molay. Paris: Les Belles Lettres, 2023. 185 pp. ISBN: 978-2-251-45458-0. - Satora, Magdalena (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)